Analysis Of Bankruptcy Prediction Using Springate, Zmijewski, Grover. And Altman Z-Score Models On Retail Companies Listed On The Indonesia Stock Exchange - Milleniasari, Poeti Annisa; Yunita, Irni (Publisher Cv. Inara, 2024)
The retail sector plays a significant role and contributes greatly to the national economy. The slowdown in domestic economic growth and decreased consumer purchasing power have significantly impacted the retail business in Indonesia. This is evident from the high number of retail companies declared bankrupt and many large retail companies closing their stores. The aim of this study is to assess the health level of retail companies, determine the differences in scores among the research models, and evaluate the accuracy of the Springate, Zmijewski, Grover, and Altman models. This research is a quantitative study with a descriptive approach. The research objects are retail companies listed on the Indonesia Stock Exchange during the period 2019-2021. Sampling technique used is purposive sampling. The results of this study indicate that the highest accuracy level is achieved by the Grover model with an accuracy of 77.7%, followed by the Zmijewski model with an accuracy level of 72.2%. Meanwhile, the Springate and Altman models have the same accuracy level of 66.6%.